Intelligent Fuzzy Logic Controller for Improved Power Extraction of Micro Wind Turbines - Botha, Stefan; Zabihi, Nima; Dobzhanskyi, Oleksandr; Gouws, Rupert (International Journal of Engineering and Technology, 2019)
Wind turbines are one of the fastest growing forms of renewable energy. The amount of power a wind turbine extracts from the incoming wind is dependent on the rotational speed and for every wind speed there is an optimal rotational speed that will extract the most amount of power from the incoming wind. Large wind turbines incorporate active control techniques whereas micro wind turbines incorporate passive control techniques with the disadvantage of lower efficiency in controlling the rotational speed and therefore a lower amount of power can be extracted. This paper proposes the development of a new control method that alters the rotational speed of a micro wind turbine in order to improve the power extraction from the incoming wind. This was done by using a DC-DC boost converter controlled by an intelligent fuzzy logic controller on the output of the generator. The controller is also unique, since it only requires the rotational speed and power output of the wind turbine generator, therefore eliminating the difficulties in obtaining the exact wind speed due to the wake effect of the wind turbine tower, whereas the majority of controllers currently in use require the wind speed. The required change in the duty cycle of the DC-DC boost converter is determined by the controller which in turn controls the electromechanical torque of the generator. The design was simulated in Matlab®/Simulink® and practically implemented using Control Desk® and a dSPACE® DS1104 controller board on a 1 kW micro wind turbine generator. Both the simulation and experimental results indicate an improvement in the amount of power extracted by the micro wind turbine generator incorporating the controller, especially during high wind speeds.